Sports Orthopedics - Niederer D; Vogt L; Banzer W (Deutsche Zeitschrift für Sportmedizin)
Rationale: This focus review aims to describe the currentevidence on training and exercise (with a special focus on motor control) in the primary prevention, chronification prevention and recurrence prevention of low back pain.Methods: Two investigators independently performed a systematic literature research in MEDLINE (PubMed). Studies on participants who currently had, or had ever had at least one episode of non-specific low back pain or their respective control cohort were included. Only trials adopting an intervention that consisted of exercises without additional specific treatment with the aim of primary prevention, prevention of chronification or prevention of recurrences of low back pain were considered eligible. Results and Discussion: For primary prevention, exercise alone and (probably even more effective) exercise in combination with education are able to reduce the risk of acute low back pain occurrence. Considering the amount of exercise needed to be effective, an inverted u-shaped association is probable. For chronification prevention, early onset physical activity after the non-specificity diagnosis of the back pain may be helpful. Moderate evidence supports the relevance of exercise programmes after primary care for recurrence prevention. Motor control exercises might also be able to reduce the recurrence risk.KEY WORDS: MiSpEx, LBP, Sensorimotor, Neuromuscular